Functional Testing of Web-Based Input Form Using Boundary Value Analysis Technique: A Case Study on TemanTernak - Akhmad Zufar Rafif; Muhammad Faris Fadhil Islam; Muhammad Nasir; Muhammad Rafi Alexander Prayoga; Raden Muhammad Raditya Rahman; Sofiyanti Indriasari (Universitas Islam Kuantan Singingi, 2025)
Software reliability is highly dependent on robust data validation mechanisms to prevent data integrity issues. The main issue raised in this study is the risk of input errors in the